2018
DOI: 10.4236/ojped.2018.84037
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Heart Disease in Côte d’Ivoire: Retrospective Multicentric Study about 228 Cases

Abstract: Introduction: In Côte d'Ivoire, the paediatrician has to face a diagnosis and management problem in front of pediatric heart disease, with consequent a high lethality. Objective: To describe the epidemiological, diagnostic, therapeutic and progressive aspects of childhood cardiopathy for the improvement of prognosis and professional practice. Materials and methods: This was a multicenter retrospective and descriptive study conducted from January 2011 to March 2016 in two main hospitals universities, one locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In this study, hospital prevalence was 14.9%. This is higher than that of Cao (0.6%) [9] in Yunnan Région of China, of Kinda in Burkina Faso (0.98%) [7] and those of several African authors, with prevalences ranging from 0.23% in Côte d'Ivoire in a multicenter study [6] to 6% in Burkina Faso [10]. This disparity in prevalence can be explained by methodological differences.…”
Section: Epidemiological Aspectsmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, hospital prevalence was 14.9%. This is higher than that of Cao (0.6%) [9] in Yunnan Région of China, of Kinda in Burkina Faso (0.98%) [7] and those of several African authors, with prevalences ranging from 0.23% in Côte d'Ivoire in a multicenter study [6] to 6% in Burkina Faso [10]. This disparity in prevalence can be explained by methodological differences.…”
Section: Epidemiological Aspectsmentioning
confidence: 83%
“…In 2018, a multicentre hospital analysis of congenital heart disease in Côte d'Ivoire revealed a hospital prevalence of 2.3‰ admissions with delayed diagnosis, before the age of 2 years, in 96.4% at the time of respiratory difficulty [6].…”
Section: Introductionmentioning
confidence: 99%
“…Heart disease has been the subject of very few studies in children in Côte d'Ivoire as well, and all of these studies have been conducted in Abidjan, so the national prevalence of childhood heart disease is unknown. One retrospective study from a few hospital-based studies found a total of 49,760 admissions, including 228 infantile heart disease cases, with a prevalence of 4.6 percent [12]. Another retrospective research studied open heart surgery between 1978 and 2013, in which the most frequent CHD were VSD (n = 240), ASD (n = 200), partial atrioventricular sepal defect (n = 30) and ToF (n = 220), and rheumatic heart disease (RHD) was 1,475 cases [13].…”
Section: Congenital Heart Disease In Ethiopia and Côte D'ivoirementioning
confidence: 99%